Palestinian Asylum Seekers, Statelessness, and the Limits of Forced Repatriation - Gabbay, Shaul M. (Advances in Social Sciences Research Journal, 2026)
Palestinian asylum seekers present a distinct and frequently misunderstood profile in contemporary asylum proceedings. Unlike most asylum-seeking populations, Palestinians often lack citizenship in any state, rendering conventional assumptions about nationality, origin, and the availability of return fundamentally inapplicable to their cases. This article examines two principal populations: Palestinians who have resided in Gulf states, primarily Saudi Arabia, the United Arab Emirates, and Kuwait, under temporary and contingent residency arrangements, and Palestinians who have fled the West Bank directly. For both groups, the assumption that "Palestine" constitutes a viable destination for forced repatriation is factually untenable. The absence of Palestinian statehood, Israeli control over all entry points into Palestinian territories, and enduring conditions of instability and persecution make return either structurally impossible or deeply unsafe. For a significant subset of applicants, individual persecution grounds including sexual orientation, religious conversion, and honor-based violence further preclude safe return. Understanding the factual dimensions of Palestinian statelessness and territorial conditions is essential for accurate and just assessment of Palestinian asylum claims.